Sensory, nutrition and physiochemical properties of beef in relation to their genotype - Hashem, MA; Hossain, MS; Ahmmed, A; Begum, S; Sadakuzzaman, M (Meat Research, 2024)
The study aimed to evaluate the sensory, nutritional, and physicochemical characteristics of meat from crossbred cattle (CBC) and indigenous cattle (IC) at different time intervals. Samples of M. longissimus dorsi muscle were collected from three Holstein-Friesian crossbred cattle and three indigenous cattle in the Mymensingh district. The analysis included two treatments based on cattle genotype and time intervals, labeled T0 (0 hours) and T24 (24 hours), and was conducted using a 2×2 factorial design in a completely randomized format. The study assessed various factors such as sensory attributes (color, flavor, tenderness, juiciness, overall acceptability), proximate composition (dry matter, crude protein, ether extract, ash), and physicochemical properties (pH, cooking loss, drip loss, water holding capacity, CIE L*, a*, b*, saturation index, and hue angle). Results showed no significant difference in color, flavor, and overall acceptability between the two treatments. However, juiciness was significantly (p<0.05) higher in IC (3.83) compared to CBC (3.17). While dry matter, crude protein, and ether extract did not differ significantly between the two groups, ash content was significantly higher in IC (1.48) compared to CBC (1.05) (p<0.05). There were no significant differences in pH, cooking loss, drip loss, CIE L*, a*, b*, and saturation index between the two treatment groups, but water holding capacity (WHC) was significantly (p<0.05) higher in IC (96.03%) compared to CBC (92.67%). Aged meat (24 hours) showed better quality based on sensory attributes. Physicochemical properties like pH and WHC decreased over time, while cooking loss and hue angle increased at the 24-hour mark.